Quality of life of children with Short Bowel Syndrome from patients’ and parents’ points of view - Kießling, Charlotte; Wessel, Lucas; Felcht, Judith; Hagl, Cornelia Irene; Boettcher, Michael; Khasanov, Rasul (Children, 2024)
Despite limited research, existing studies using generic quality of life (QOL) tools indicate decreased physical health and compromised emotional functioning in children with IF. This study investigates QOL in children with short bowel syndrome (SBS) and its determinants. The study included 57 pediatric patients with SBS treated at Mannheim’s University Hospital between 1998 and 2014. To evaluate QOL, the KINDL questionnaire was used. Three age-specific questionnaire variants were employed, and parental proxy reports were collected. Most patients underwent intestinal lengthening procedures, with varying primary diagnoses. A comparison with healthy children from the patient’s perspective revealed no difference but from the parent’s perspective showed lower QOL in SBS patients, especially regarding physical and mental well-being. QOL varied with age, with 7-10-year-olds reporting the lowest scores. Several factors, including independence from parenteral nutrition and the presence of a complete colon, positively influenced QOL. The independence of parenteral nutrition and the presence of a complete colon positively influenced QOL. The Bianchi technique for intestinal lengthening has also shown promise but needs further research. The observation sample in this study is too small to generalize about the whole population of SBS patients. However, this study shows that many health and treatment factors affect QOL, and a large multicenter study is necessary. Our findings underline the importance of appropriate psychological support for children with SBS and their families.
Gesehen am 11.12.2024